2010
DOI: 10.1375/ajgc.20.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying as an Act of Revenge?

Abstract: Despite significant overlaps between victim status in traditional forms of bullying and cyberbullying, and qualitative results about self-reported reasons for cyberbullying, the role of revenge and retaliation as a motive to engage in acts of cyberbullying has not yet been examined systematically. As a first step, this study investigates whether and to what extent traditional victims, when they become cyberbullies, actually choose their former (traditional) perpetrators as targets of their own cyberbullying be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 33 publications
9
79
1
9
Order By: Relevance
“…Most researchers agree that it is distinguished in two dimensions, cognitive empathy (i.e. the ability to recognize and understand others' feelings), and affective empathy which involves arousal to others' emotional state (König, Gollwitzer, & Steffgen, 2010). Cognitive empathy is related to Theory of Mind and perspective taking and is a prerequisite for experiencing affective empathy (Blair, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers agree that it is distinguished in two dimensions, cognitive empathy (i.e. the ability to recognize and understand others' feelings), and affective empathy which involves arousal to others' emotional state (König, Gollwitzer, & Steffgen, 2010). Cognitive empathy is related to Theory of Mind and perspective taking and is a prerequisite for experiencing affective empathy (Blair, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of choice theory and reality therapy on cyber-bullying behaviors is about not giving importance to the effects of past and focusing on present in relation to the source of behaviors (Corey, 2009). Studies show that those with cyber-bullying behaviors were exposed to cyber or traditional bullying in their past (König et al, 2010). In addition, another finding of studies is that cyber-bullying and parental attitudes during childhood are related (Dilmaç and Aydogan, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that people displaying cyberbullying behaviors do not feel safe (Sourander et al, 2010); they feel alone (Schoffstall and Cohen, 2011), have feelings of revenge (König et al, 2010;Raskauskas and Stoltz, 2007) and are hostile (Arıcak, 2009) feelings. Besides, these people stated that a reason behind their Tanrikulu 663 cyberbullying behaviors is to get rid of boredom (Yaman and Peker, 2012).…”
Section: Total Behavior and Cyberbullyingmentioning
confidence: 99%
“…Persons who describe themselves as being cyberbullies get the support of their peers and often times they do nothing to stop their friends from engaging in such deviant behaviour even though they see the effects (Spears et al, 2009). Revenge or getting back at peers and anger are some of the main reasons persons engage in cyberbullying (Konig et al 2010). Cyberbullying is quite common in instances where intimate and peer relationships undergo stress such as a sudden breakup, envy and intolerance of others because of minor indifferences (Hoff and Mitchell, 2009).…”
Section: Literature Surveymentioning
confidence: 99%